The Binding Of Bifidobacterium Pseudocatenulatum G4 Tomutagenic/Carcinogenic Heterocyclic Aromatic Aminesin An In Vitro Study - Faridnia, Farnaz (2010)

(untitled)
Consumption of probiotic microorganisms has been associated with decreased risk of colon cancer and reported to have antimutagenic/anticarcinogenic properties. Lactic acid bacteria (LAB) existing in the colon may exert an anticarcinogenic action, but the mechanism is still poorly understood. One possible mechanism for this effect involves physical binding of the mutagenic compounds, such as heterocyclic amines, to the bacteria. Therefore, the purpose of this study was to study the binding assay of mutagenic/carcinogenic heterocyclic aromatic amines (HCAs) to Bifidobacterium pseudocatenulatum G4, a species which has not been explored yet as a commercial probiotic, in vitro. The effect of two gram positive bacteria: Bifidobacterium pseudocatenulatum G4 and Bifidobacterium longum BB536 (a commercial probiotic used as a reference strain), and a gram negative bacterium: human intestinal strain Escherichia coli ATCC 25922 at the colon environmental pH and temperature were studied.